The Influence of Employer Branding on Intention to Apply at PT X in Tangerang Selatan: Study on @Rekrutmensks Instagram Account Followers - Nadya Najla Feranda; Herwan Abdul Muhyi; Pratami Wulan Tresna (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the influence of employer branding on intention to apply at PT X. This influence is measured through employee and prospective employee perceptions of the company's image as an attractive place to work. The research method used was a survey with a questionnaire as a data collection instrument. Respondents consisted of the audience of PT X is employer branding Instagram account called @kerjamensks. The research results show that employer branding has a positive effect on intention to apply, where positive perceptions of the company's image increase prospective employees' interest in applying for jobs. These findings have the implication that a company's efforts to build a positive image as a workplace can influence prospective employees' decisions to join the company. Therefore, companies are advised to continue to improve their employer branding strategies in order to attract and retain quality human resources.